Inhibition of Macrophage Functions by the C-Terminus of Murine S100A9 Is Dependent on B-1 Cells - Pagano, Rosana Lima; Moraes, Natassja Foizer; De Lorenzo, Beatriz Helena; Coccuzzo Sampaio, Sandra; Mariano, Mario; Giorgi, Renata (Mediators of Inflammation, 2014)
The protein S100A9 plays a key role in the control of inflammatory response. The C-terminus of the murine S100A9 protein (mS100A9p) downregulates the spreading and phagocytic activity of adherent peritoneal cells. Murine peritoneal cells are constituted by macrophages and B-1 cells, and the latter exert an inhibitory effect on macrophage functions by secreting interleukin- (IL-) 10. Here, we investigated the influence of B-1 cells on the inhibitory effect evoked by mS100A9p on macrophages. mS100A9p did not alter spreading and phagocytosis either by peritoneal macrophages obtained from mice deprived of B-1 cells or by bone marrow-derived macrophages (BMDMϕ). Nevertheless, when BMDMϕ were cocultivated by direct or indirect contact with B-1 cells treated with mS100A9p, the phagocytosis by BMDMϕ was decreased, showing that the effect of mS100A9p on macrophages was modulated by B-1 cells and/or their secretory compounds. Furthermore, the inhibitory action of mS100A9p on phagocytosis by adherent peritoneal cells was abolished in cells obtained from IL-10 knockout mice. Taken together, the results show that mS100A9p has no direct inhibitory effect on macrophages; however, mS100A9p modulates B-1 cells, which in turn downregulates macrophages, at least in part, via IL-10. These data contribute to the characterization of S100A9 functions involving B-1 cells in the regulation of the inflammatory process.